1996
DOI: 10.1111/j.1744-7348.1996.tb07106.x
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence in cereal aphid populations

Abstract: Long sequences of data on the incidence of cereal aphids from five European countries were analysed for evidence of density dependent processes occurring between years. Using a randomisation test (Pollard, Lakhani & Rotheray, 1987), density dependence was revealed in all (16) population censuses of Metopolophium dirhodum, 60% of Rhopalosiphumpadi censuses (10 of 17) but only 25% of Sitobion avenue population censuses (4 of 16). Correcting for density independent effects of weather revealed the existence of sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…We were unable to Þnd any temperature relationship under South Carolina conditions. Rhopalosiphum padi populations in cereals have also been positively correlated with preceding summer rainfall (Plumb 1995, Maudsley et al 1996, however, we found no signiÞ-cant correlation. In our studies, barley yellow dwarf incidence was primarily dependent on the development of R. padi colonies during February and March.…”
Section: Discussioncontrasting
confidence: 71%
“…We were unable to Þnd any temperature relationship under South Carolina conditions. Rhopalosiphum padi populations in cereals have also been positively correlated with preceding summer rainfall (Plumb 1995, Maudsley et al 1996, however, we found no signiÞ-cant correlation. In our studies, barley yellow dwarf incidence was primarily dependent on the development of R. padi colonies during February and March.…”
Section: Discussioncontrasting
confidence: 71%
“…Density-dependent feedbacks have been reported previously for aphid populations for which long-term data sets are available (Sequeira & Dixon, 1997), and density-dependent population Table 2. For instance, Maudsley et al (1996) found that approximately 60% of the European R. padi populations they observed exhibited density-dependent population growth, and 100% of the M. dirhodum populations they tested exhibited density-dependent regulation. Values are coefficients of determination (R 2 ) for linear regressions of log-transformed interannual aphid population abundances, N t , on climate metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Aphids (Homoptera: Aphididae) have complex population dynamics often characterized by wide variations of population density, both on a temporal and spatial scale. Analyses of long time-series data reveal that density dependent processes commonly regulate populations of aphids within and between years (Woiwod and Hanski, 1992;Maudsley et al, 1996;Sequeira and Dixon, 1997;Jorošík and Dixon, 1999). Interactions among aphids and their host-plant largely contribute to the regulation of aphid populations, through the intrinsic quality of host plants (Kidd, 1990;Karley et al, 2003) or intraspecific competition on crowded plants resulting in an elevated level of mortality, low reproductive success, and high rate of dispersal among aphids (Dixon, 1971(Dixon, , 1998Day, 1986;Klindmann and Dixon, 1996).…”
Section: Introductionmentioning
confidence: 99%